PENGARUH KONVERGENSI IFRS TERHADAP KUALITAS INFORMASI AKUNTANSI DENGAN COUNTRY BUSINESS ENVIRONMENT SEBAGAI VARIABEL MODERATING - Naufal Rheza Pratama; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
Accounting information stated in the financial statement can be biased and irrelevant for the sake of decision making if the company's management performs earnings management actions. In addition, the variety of accounting standards used in various countries also contribute to reducing the relevance of accounting information for decision making due to lack of comparability aspects in related financial statements. This research attempts to investigate whether the IFRS convergence occurring in Indonesia, Malaysia, and Thailand, is able to improve the quality of accounting information in these countries and to investigate whether the country business environment strengthens the relationship between the IFRS convergence and the quality of accounting information. This research utilized a robust regression method, with earnings management as a proxy of dependent variable of the quality of accounting information. While IFRS convergence is the independent variable that moderated by the country business environment (CBE). The sample of this research cover manufacturing companies listed on the Indonesia Stock Exchange (BEI) spanning the period 2009-2015 with a total of 86 companies, the Thailand Stock Exchange (SET) for the period 2007-2013 with a total of 146 companies, and the Malaysia Stock Exchange (MYX) for the period 2009- 2015 with a total of 150 companies.The research results showed that the IFRS convergence in Indonesia, Malaysia and Thailand was able to increase the quality of accounting information, and revealed that the country business environment strengthened the relationship between the IFRS convergence and the quality of accounting information, especially in Indonesia, Malaysia and Thailand.